TINGKAT DAN RAGAM KONSUMSI PANGAN GOLONGAN USIA LANJUT DI PANTI WERDHA BUDI LUHUR DAN HANNA DI YOGYAKARTA - Erna Luciasari; Trintrin T. Mudjianto; Tjetjep S. Hidayat; Djoko Susanto (Persagi, 1998)
Number of the elderly is increasing relatively fast in Indonesia. It is estimated by the US Bureau of the Cencus that this country will be the fourth in the world regarding the big number of it. As they are becoming older the physiological functions become weaker, it includes the function of intestine which influence the kind of food they can eat. This study has been carried out as to collect information's regarding level and variety of foods consumed by the elderly. A number of 53 elderly reside in two nursing homes, i.e. Budi Luhur and Hanna in Yogyakarta have been involved in the study. Important results show that most of the elderly used to eat main dish meal three times and snacks one-two time daily. The main staple food is rice which contributes 60-70% of total energy intake. Foods of fat sources contribute 15-20% of energy intake. Foods of animal protein sources are consumed 30-50 gram daily, and 50-100 gram of plant protein sources such as fermented soybean (tempe). Drinking water are drunk 6-9 glasses a day. By consuming such level and variety of foods, 47% of elderly are relatively thin, 47% sedentary and 6% relatively obese.Keywords: foods consume, elderly, nursing home